Antibacterial and Bactericidal Effects of the Er: YAG Laser on Oral Bacteria: A Systematic Review of Microbiological Evidence - Jakub Fiegler-Rudol; Dariusz Skaba; Aleksandra Kawczyk-Krupka; Rafał Wiench (Journal of Functional Biomaterials, 2025)
Background: The Er:YAG laser has gained attention in dentistry for its potential to enhance microbial disinfection through targeted photothermal and photoacoustic mechanisms. Objective: This systematic review aimed to evaluate the antibacterial and bactericidal efficacy of Er:YAG laser therapy across clinically relevant oral pathogens in in vitro models. Methods: Following the PRISMA 2020 guidelines, a systematic search of PubMed, Embase, Scopus, and the Cochrane Library was conducted for studies published between 2015 and 2025. The review protocol was registered with PROSPERO (CRD420251031368). Eligibility criteria included in vitro or animal studies assessing the bactericidal effects of the Er:YAG laser on oral bacteria or fungi, either alone or in combination with chemical disinfectants. Study selection, data extraction, and quality assessment were conducted independently by multiple reviewers. Results: Ten in vitro studies met inclusion criteria. The Er:YAG laser demonstrated significant antibacterial effects against Enterococcus faecalis, Streptococcus mutans, Porphyromonas gingivalis, Candida albicans, and other species. Greater bacterial reduction was consistently observed when the laser was combined with adjunctive irrigants such as sodium hypochlorite or hydrogen peroxide. The laser was effective in reducing biofilm biomass and viable counts, particularly in complex anatomical settings. Most studies were rated as low risk of bias. Conclusions: Er:YAG laser therapy is a promising adjunctive tool for microbial disinfection in dentistry, particularly in challenging anatomical sites. Further well-designed in vivo and clinical studies are needed to confirm its efficacy and determine optimal treatment parameters.